48. OBSERVING THE IMPACT OF EMBRYO CULTURING CONDITIONS ON NON-INVASIVE PREIMPLANTATION GENETIC TESTING FOR ANEUPLOIDY DETECTION (NI-PGT-A). (August 2019) - Jasper, M.; Robinson, C.
Abstract : Introduction: There are several options available to clinics culturing IVF embryos, including group and individual droplet culture, sequential or single-step medium culture and the possibility to renew the medium during culture. The absence of standardised culturing conditions or molecular testing methodologies, including whole genome amplification (WGA) used for non-invasive preimplantation genetic testing for aneuploidy (NI-PGT-A) may explain the variable rates of concordance reported between the spent embryo culture media and embryo biopsy results to-date. Culture conditions contribute to the accumulation of embryonic and contaminating DNA in spent embryo culture media. Optimisation of either the culturing conditions, molecular testing methodologies, or both, should yield the highest accuracy results for NI-PGT-A. This study examined rates of concordance between spent embryo culture media and embryo biopsies with the aim of evaluating the impact of culturing conditions on NI-PGT-A results. Material and methods: Spent embryo culture media was collected from single embryo culture droplets following biopsy of the embryo for PGT-A, then stored at -20°C, with ethics approval. Spent embryo culture media samples from 10ul-60ul culture droplets were whole genome amplified using DOPlify® kit reagents (PerkinElmer). WGA DNA yield was assessed following gel electrophoresis and high sensitivity Qubit instrument quantification (ThermoFisher). Next generation sequencing libraries and sequencing was performed according to the standard PG-Seq TM kit 48 sample protocol on a MiSeq® instrument sequencer (Illumina). Data was bioinformatically aligned to hg19 and analysed using PG-Seq TM kit software. WGA DNA yield, NGS metrics, and whole chromosome aneuploidy concordance with the PGT-A result for the embryo biopsy were determined. Results: Results were collated for each set of culturing conditions, including whether the media was renewed during culture. Whole genome amplification using DOPlify® kit reagents resulted in the amplification of 78-100% of spent embryo culture media samples (WGA failure rate 0-22%). Ploidy concordance with the embryo biopsy ranged from 33-55% for autosomal chromosomes and 47-53% for sex chromosomes using a single-step culturing system (n=3 protocols), compared with concordance rates of 60-95% and 50-97% respectively when media was changed during the 5-6 day culture (n=4 protocols). Conclusions: Successful NI-PGT-A using spent embryo culture media will possibly require specific culturing conditions and/or specialised molecular methodologies for accurate and representative amplification and testing of the embryonic DNA. In a step toward this, we identified that renewing culture media during IVF improves overall concordance rates between the embryo biopsy and spent embryo culture media for NI-PGT-A.